Tolvaptan: a possible preemptive treatment option in children with autosomal dominant polycystic kidney disease? - Hee Sun Beak; Min Hyun Cho (Korean Society of Pediatric Nephrology, 2023)
Tolvaptan is a highly selective vasopressin receptor 2 antagonist that regulates cyclic adenosine monophosphate levels to inhibit both epithelial cell proliferation and chloride ion excretion, two mechanisms known to induce cyst expansion in autosomal dominant polycystic kidney disease (ADPKD). Tolvaptan is currently the preferred treatment of rapidly progressive disease ADPKD in adult patients; however, since cyst formation in ADPKD begins early in life, (frequently in utero), and significant disease progression with cyst expansion occurs in the first decade, tolvaptan may be advantageous as a preemptive treatment in children with ADPKD. Tolvaptan has already been used to successfully treat refractory edema or hyponatremia in children; this literature review provides insight into the biochemical basis of its action to contextualize its use in the pediatric population.